Arenaria radians as a synonym of Arenaria dicranoides (Caryophyllaceae): morphological insights with additional notes - Trujillo, Emilio J.; Romoleroux, Katya; Muriel, Priscilla (Phytotaxa, 2026)
The genus Arenaria in Ecuador has not been well approached in a taxonomic way, leading to several misinterpretations throughout the time. Based on worldwide databases, ten accepted Arenaria species would occur in the country. As part of an ongoing work towards a new volume of the series Flora of Ecuador, we have verified that two endemic species (A. radians and A. dicranoides) belong to the same taxon and their names should be treated as heterotypic synonyms. Notes regarding the morphology of Arenaria dicranoides (which have nomenclatural prioritiy on Arenaria radians), its distribution, ecology, and an updated conservation assessment are provided.